PERSEPSI PASIEN DAN DOKTER TENTANG PENTINGNYA INFORMED CONSENT TERTULIS DALAM TINDAKAN TRANSFUSI DARAH DI RUMAH SAKIT UMUM DAERAH dr. SOEDIRAN MANGUN SUMARSO WONOGIRI - , HASLINDA RINTO RAHAYU, dr. Siswanto Sastrowijoto,Sp.THT-KL (K).,MH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Blood transfusion is one of many activities carried out in hospitals. It may bring numerous unexpected effects such as allergy that can cause extended length of stay of patients which results in increase of hospitalization cost, morbidity and mortality. Informed consent is the media used by the physicianto transfer knowledge to patients. Informed consent is regulated by law which becomes physicians obligation and patientsâ autonomous rights. Informed consent of medical intervention in Indonesia is available but not in blood transfusion intervention. Objective: The objective of the study was to compile draft of written informed consent in blood transfusion intervention. Method: The study was descriptive qualitative. Instrument of the study was indepth interview with patients, physicians and hospital management. Result and Discussion: The results of the showed study written informed consent was obtained that contained transfusion intervention 7 respondents said it was important for existing patients and physicians all respondents to give the same statement. Informed consent should be implemented according to perception of the patient, physician, and hospital management due to the risk that such an intervention might bring, need for hospital accreditation, and legality of physicians intervention. Component of informed consent intervention blood transfusion in writing in accordance with the patient and physician perception is the reason blood transfusion, side effects or risk action, the amount of blood per pack and patient consent will be intervention. Conclusion and Suggestion: Written informed consent component in blood transfusion according intervention perceptions of patients, physicians, management and regulations in Indonesia included: indications, objectives, risks or side effects of actions, alternatives intervention in addition to blood transfusion, blood counts, implementation procedures, prognosis and intervention costs of blood per pack